4-Nitrochalcone as a potential drug in non-clinical breast cancer studies - Galindo, Claudia Martins; Milani, Letícia; de Lima, Lucas Trevisan França; Adami, Eliana Rezende; Go, Simei; de Noronha, Lucia; Beltrame, Olair Carlos; Klassen, Giseli; de Souza Ramos, Edneia Amancio; Elferink, Ronald P.J. Oude; Acco, Alexandra (Chemico-biological interactions, 2024)
Breast cancer is a high-magnitude public health problem, continually challenging physicians and scientists worldwide in the field of drug therapy. 4-nitrochalcone (4NC) is a phenolic compound that has promising antitumor activity in vitro, but its application in breast cancer treatment is still poorly explored. This study aimed to evaluate the action of 4NC in vitro and in vivo breast cancer models. The cytotoxic potential of 4NC was tested towards MCF-7 and MDA-MD-231 breast cancer cells, with a lower impact in the non-tumor lineage HB4a. For in vivo studies, solid Ehrlich carcinoma (SEC) was used, a syngeneic mouse model with non-nuclear estrogen and progesterone positivity, characterized by immunohistochemistry. Daily oral administration of 4NC (25 mg kg−1) for 21 days led to a consistent reduction in tumor growth compared to the vehicle group. No signs of toxicity evaluated by hematological, biochemical, histological, and oxidative stress parameters were observed in mice, and the DL50 was >2000 mg kg−1. The effectors Raptor and S6K1 showed decreased activation, with a consequent reduction in protein synthesis; concomitantly, there was an increase in LC3-II levels, but the protective autophagic response was not completed, with the maintenance of p62 levels and cell death. These results open new possibilities for the use of 4NC as a tumor cell metabolism modulating agent. [Display omitted] •4-nitrochalcone (4NC) was effective in reducing breast cancer in vivo and in vitro.•4NC attenuates the mTORC1-Raptor/S6K1 pathway and blocks autophagy.•The DL50 of 4NC was >2000 mg kg−1.•4NC affected the lactate/pyruvate ratio, an important indicator of the Warburg effect on tumor cells.•Solid Ehrlich carcinoma (SEC) has cytoplasmic estrogen and progesterone signaling.